2005
DOI: 10.1021/es050794n
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Fenton Degradation of Diclofenac:  Identification of Main Intermediates and Degradation Pathway

Abstract: In recent years, the presence of pharmaceuticals in the aquatic environment has been of growing interest. These new contaminants are important because many of them are not degraded under the typical biological treatments applied in the wastewater treatment plants and represent a continuous input into the environment. Thus, compounds such as diclofenac are present in surface waters in all Europe and a crucial need for more enhanced technologies that can reduce its presence in the environment has become evident.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
97
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(120 citation statements)
references
References 37 publications
13
97
0
6
Order By: Relevance
“…In a pilot-scale study of the removal of diclofenac by photo-Fenton's reagent using a compound parabolic collector (CPC) exposed to sunlight, complete oxidation was attained within 60 min, and complete mineralization in 100 min. 98 Comparison with other oxidative treatments, namely O 3 , UV/H 2 O 2 and photolysis, showed that degradation pathways differed between these AOPs. Similarly, Radjenovic et al 99 found similar, but not identical pathways for the degradation of atenolol by heterogeneous photocalatyis and homogeneous photo-Fenton treatment in the same CPC setup.…”
Section: B4 Ppcp Transformation During Ozonationmentioning
confidence: 97%
“…In a pilot-scale study of the removal of diclofenac by photo-Fenton's reagent using a compound parabolic collector (CPC) exposed to sunlight, complete oxidation was attained within 60 min, and complete mineralization in 100 min. 98 Comparison with other oxidative treatments, namely O 3 , UV/H 2 O 2 and photolysis, showed that degradation pathways differed between these AOPs. Similarly, Radjenovic et al 99 found similar, but not identical pathways for the degradation of atenolol by heterogeneous photocalatyis and homogeneous photo-Fenton treatment in the same CPC setup.…”
Section: B4 Ppcp Transformation During Ozonationmentioning
confidence: 97%
“…2 These contaminants are important because many of them are not degraded by the typical biological treatments applied in wastewater treatment plants and represent a continuous input into the environment. 3 Within the aquatic environment, in river and surface waters, diclofenac is one of the most frequently detected pharmaceuticals. 4 Diclofenac is considerably stable under normal environmental conditions and the most probable decomposition pathway for its onsite elimination is photodecomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Observando ainda o decaimento da concentração do fármaco, verificou-se que a degradação do diclofenaco está associada diretamente à corrente aplicada ao sistema, pois as maiores correntes alcançaram as maiores reduções do diclofenaco e em um menor tempo de experimento. [6][7][8][9] Diversos trabalhos publicados mostram que a degradação de compostos via H 2 O 2 ocorre através do ataque do • OH na molécula orgânica, porém esse ataque é lento devido à baixa taxa de conversão do H 2 O 2 em • OH; devido a esse fato, ocorreu um acúmulo de peróxido residual, no qual o tempo de eletrólise não foi suficiente para a conversão para…”
Section: Estudo Da Degradação Do Diclofenaco Sódicounclassified
“…[6][7][8][9][13][14][15][16][17][18][19][20] Na Figura 6 observa-se o comportamento da concentração do diclofenaco durante as eletrólises no reator na presença de íons Fe 2+ . A concentração do fármaco diminui rapidamente nos primeiros 20 min de experimento, comportamento que se reproduz em todas as eletrólises.…”
Section: Estudo Da Degradação Do Diclofenaco Sódicounclassified
See 1 more Smart Citation